Trail guide to the body - Biel, Andrew (Books of Dicovery, 2005)
If you want to differentiate your psoas from your scalenes or just want to ace the next quiz, you'll find the answer here. This handbook follows the chapters and structures as they are arranged in the Trail Guide to the Body textbook. A resourceful complement, this handbook contains 200 pages and 450 illustrations. It offers a variety of questions and exercises including fill-in-the-blanks, drawings to color, illustrations and matching exercises. A fun learning tool that will test a student's Trail Guide knowledge